Determination of required anatomical knowledge for clinical practice in emergency medicine: national curriculum planning using a modified Delphi technique. Issue 9 (18th August 2006) - Kilroy, D; Driscoll, P
Abstract : Objectives: To identify the content of the postgraduate anatomy curriculum for trainees in emergency medicine (EM) in the UK. Methods: Modified Delphi technique involving 160 randomly sampled consultants in EM. The outcome measure was percentage agreement, based upon a three round iterated Delphi process, of participants to items derived from a standard anatomy text being core knowledge for postgraduate clinical practice in the specialty. A national curriculum document was derived as a result of the data obtained. Results: Response rates ranged from 61% to 70% after three Delphi rounds. From an initial overall questionnaire content of 808 discrete items, 64% was retained as core required knowledge following iteration. This formed the basis of a national consensus anatomy curriculum both to inform question development in postgraduate EM examinations and to benchmark anatomical knowledge requirements for safe clinical practice. Conclusions: Application of a national consensus methodology allows for determination of curricular content in anatomy. The principles can be applied to all aspects of training and curricular policy at national collegiate level to guide the development of robust documentation.